Music, text and context in Felix Mendelssohn’s choral works for Berlin Cathedral - Flanagan, Orla (Royal Irish Academy of Music, 2016)
Although the towering presence of Mendelssohn’s oratorios has dominated the scholarship on his choral music, new light has recently been shed upon some of the shorter vocal works. During Mendelssohn’s tenure as Generalmusikdirektor (Royal Composer of Church Music) at Berlin Cathedral from 1843 to 1844, he composed several fine liturgical pieces. However, various frustrations at Berlin Cathedral appear to have cut short Mendelssohn’s career there, ultimately causing him to seek release from his duties in 1844. This thesis examines the religious background and overall context surrounding the Berlin Cathedral period of Mendelssohn’s career in order to enable a more complete understanding of the music and its legacy. The composer’s stature as a Neuchrist is considered with a view to elucidating his approach to the composition of sacred music. A detailed investigation of the Berlin Cathedral music focuses upon two principal aspects: text and style. A new argument is presented for innovation in Mendelssohn’s treatment of text insofar as is evidenced in the a cappella works written for Berlin Cathedral, including Drei Psalmen, Op.78 Sechs Sprüche, Op.79, and Die Deutsche Liturgie. The question of influence has always weighed heavily upon Mendelssohn scholarship; this study will address Mendelssohn’s use of earlier styles with particular reference to Palestrina and the Italian polychoral music of the Sistine Chapel, as has been explored by James Garratt and others. Finally, new light is shed on the extent to which, with his Berlin Cathedral choral music, the ‘epigonal’ Mendelssohn left a legacy for his German contemporaries and successors, Schumann and Brahms.
Keywords: Music; Musicology; Mendelssohn-Bartholdy, Felix, 1809-1847--Criticism and interpretation; Choral music, Sacred--19th century